Descontaminação de máscaras N95 em hospital público de Belém/PA: apresentação e avaliação de protocolo simplificado - MATTOS, Simone Lopes de (Universidade Federal do Pará, 2025)
he author presents a protocol for decontamination of N95 filter masks by means of short wave ultraviolet irradiation (UV-C), as well as the results of the microbiological validation testing of the UV-C device and qualitative research on the adherence of professionals from the João de Barros Barreto University Hospital, of the University Hospital Complex of the Federal University of Pará (HUJBB) to the aforementioned protocol. The microbiological tests demonstrated the efficacy of the decontamination protocol, as there was no bacterial growth in culture media inoculated with swabs of masks used in the hospital and decontaminated in the UV-C device, which proved the germicidal efficiency of UV-C irradiation. The results of the qualitative research point to the adherence of nursing professionals to the practice of mask decontamination, recognizing the practicality and contribution of the protocol to biosafety and occupational safety. As part of the same protocol, an alternative packaging for storing masks in the intervals of use of N95 masks is presented, considering their safe reuse. The protocol also has the following advantages: low cost and practicality of use, in addition to contributing to the reduction of infectious waste. Descriptors: Decontamination. Ultraviolet Rays. Radiation Dosimeters. Personal Protective Equipment. Respiratory Protection Devices. biosecurity.he author presents a protocol for decontamination of N95 filter masks by means of short wave ultraviolet irradiation (UV-C), as well as the results of the microbiological validation testing of the UV-C device and qualitative research on the adherence of professionals from the João de Barros Barreto University Hospital, of the University Hospital Complex of the Federal University of Pará (HUJBB) to the aforementioned protocol. The microbiological tests demonstrated the efficacy of the decontamination protocol, as there was no bacterial growth in culture media inoculated with swabs of masks used in the hospital and decontaminated in the UV-C device, which proved the germicidal efficiency of UV-C irradiation. The results of the qualitative research point to the adherence of nursing professionals to the practice of mask decontamination, recognizing the practicality and contribution of the protocol to biosafety and occupational safety. As part of the same protocol, an alternative packaging for storing masks in the intervals of use of N95 masks is presented, considering their safe reuse. The protocol also has the following advantages: low cost and practicality of use, in addition to contributing to the reduction of infectious waste. Descriptors: Decontamination. Ultraviolet Rays. Radiation Dosimeters. Personal Protective Equipment. Respiratory Protection Devices. biosecurity.he author presents a protocol for decontamination of N95 filter masks by means of short wave ultraviolet irradiation (UV-C), as well as the results of the microbiological validation testing of the UV-C device and qualitative research on the adherence of professionals from the João de Barros Barreto University Hospital, of the University Hospital Complex of the Federal University of Pará (HUJBB) to the aforementioned protocol. The microbiological tests demonstrated the efficacy of the decontamination protocol, as there was no bacterial growth in culture media inoculated with swabs of masks used in the hospital and decontaminated in the UV-C device, which proved the germicidal efficiency of UV-C irradiation. The results of the qualitative research point to the adherence of nursing professionals to the practice of mask decontamination, recognizing the practicality and contribution of the protocol to biosafety and occupational safety. As part of the same protocol, an alternative packaging for storing masks in the intervals of use of N95 masks is presented, considering their safe reuse. The protocol also has the following advantages: low cost and practicality of use, in addition to contributing to the reduction of infectious waste. Descriptors: Decontamination. Ultraviolet Rays. Radiation Dosimeters. Personal Protective Equipment. Respiratory Protection Devices. biosecurity.he author presents a protocol for decontamination of N95 filter masks by means of short wave ultraviolet irradiation (UV-C), as well as the results of the microbiological validation testing of the UV-C device and qualitative research on the adherence of professionals from the João de Barros Barreto University Hospital, of the University Hospital Complex of the Federal University of Pará (HUJBB) to the aforementioned protocol. The microbiological tests demonstrated the efficacy of the decontamination protocol, as there was no bacterial growth in culture media inoculated with swabs of masks used in the hospital and decontaminated in the UV-C device, which proved the germicidal efficiency of UV-C irradiation. The results of the qualitative research point to the adherence of nursing professionals to the practice of mask decontamination, recognizing the practicality and contribution of the protocol to biosafety and occupational safety. As part of the same protocol, an alternative packaging for storing masks in the intervals of use of N95 masks is presented, considering their safe reuse. The protocol also has the following advantages: low cost and practicality of use, in addition to contributing to the reduction of infectious waste. Descriptors: Decontamination. Ultraviolet Rays. Radiation Dosimeters. Personal Protective Equipment. Respiratory Protection Devices. biosecurity.he author presents a protocol for decontamination of N95 filter masks by means of short wave ultraviolet irradiation (UV-C), as well as the results of the microbiological validation testing of the UV-C device and qualitative research on the adherence of professionals from the João de Barros Barreto University Hospital, of the University Hospital Complex of the Federal University of Pará (HUJBB) to the aforementioned protocol. The microbiological tests demonstrated the efficacy of the decontamination protocol, as there was no bacterial growth in culture media inoculated with swabs of masks used in the hospital and decontaminated in the UV-C device, which proved the germicidal efficiency of UV-C irradiation. The results of the qualitative research point to the adherence of nursing professionals to the practice of mask decontamination, recognizing the practicality and contribution of the protocol to biosafety and occupational safety. As part of the same protocol, an alternative packaging for storing masks in the intervals of use of N95 masks is presented, considering their safe reuse. The protocol also has the following advantages: low cost and practicality of use, in addition to contributing to the reduction of infectious waste.